Finding Minimum and Maximum Values of Variables in Mathematical Equations by Applying Firefly and PSO Algorithm - Rouwayda Nadhim Salih; Marwa Adeeb Al-jawaherry (Tikrit Journal of Pure Science, 2020)
Computers are often used when problems are big or hard to solve. However, traditional ways to find solutions are not enough when problems are very serious. Hence, turning to nature may be the answer to find solutions for these problems. Artificial intelligence tries to simulate creatures and activities in nature turning their techniques to find solutions for a given problem into an algorithm. Although there are many algorithms have been developed, whose works are inspired by nature, there has been continuous researches aimed at finding better and faster algorithms. Many mathematical optimization problems can be solved by Swarm intelligence algorithms. The aim of this algorithm is to get the optimum solution by repeated searches whose main concern is to discover the area related to solution. In this paper, Firefly Algorithm (FA) and Particle Swarm Optimization (PSO) algorithm are executed. The two algorithms are implemented to find the minimum and maximum values of the mathematical equations. Users of the proposed system are able to read the equation directly through the execution time, by displaying and analyzing the obtained results which show that the FA algorithm has a better performance than PSO algorithm. In addition, the program is executed by MATLAB.